Africa Development Indicators 2007 : Spreading and Sustaining Growth in Africa - World Bank (Africa Development Indicators, 2007)
Africa Development Indicators 2007/8 (ADI) is the latest annual report from the World Bank on social and economic conditions across the continent. ADI is designed to provide a set of key indicators to monitor development outcomes in the region. It is an important reference tool for those who want a better understanding of the economic and social developments occurring in Africa. ADI contains statistical indicators of over 1,200 indicators and time series from 1965 for 53 countries. Data include social, economic, financial, natural resources, infrastructure, governance, partnership, and environmental indicators. It also brings an essay on a key topic for Africa, and this years' theme is the long term growth challenges of the continent